Computational thinking: an analysis through structured programming using Scratch - Kuz, Antonieta (Revista de ciencia y tecnología, 2023)
In recent years, numerous initiatives have emerged to develop computational thinking. Computational thinking and programming are closely related they are both tools for working with algorithmic concepts. ICTs and, and specifically computer programs with a playful orientation for teaching programming are relevant since they take into consideration aspects related to the educational environment. Game-based learning is a complement that allows taking advantage of the playful component of games to train computational thinking and, therefore, various others skills. Scratch is one of the most used tools to teach programming, through visual and playful programming languages that seek to promote computational skills that involve problem solving, through active and constructive learning. In this study, theoretical foundations of structured programming are analyzed based on simple computing concepts such as handling sequences, control instructions such as loops and conditionals, and their adaptation using Scratch. For this article, a qualitative analysis is presented, supported by descriptive research. The partial findings, at this point, suggest the usefulness of applying video games to train computational thinking skills. In this way, opens the possibility of proposing extended uses of other interactive games such as Lightbot, PilasEngine, Pilas Bloques.